ANALISIS PEKERJAAN PENGADAAN BAHAN BANGUNAN UNTUK RUMAH - Bakhtiar A (Politeknik Negeri Lhokseumawe, 2013)
This study explain the method at work of the wood levying by contractor at execution of housing development. Two alternatives from method purchasing which generally in contractor application is doing by self or sub-contractor. This study get the sample from three house types : simple, middle, and luxuriant. The purpose of this study is compare the levying method which is in contractor application if they get the work. The method of data collecting is survey method. Data were analyzed by using the method of ranking and look at the frequency from the results of the questionnaire. Result of study indicate that for the simple house type, is more wise to execute by self. For the type of middle and luxuriant, better of the wood work has given to sub-contractor, a type middle house of case study for the confirmation of result of the empirical study.